Diversity and spatial distribution of dragonflies (Odonata) at Soraya Research Station, Leuser Ecosystem Area, Northern Sumatra, Indonesia - SUWARNO SUWARNO; ARIFAH YASMIN SAIDI; YEKKI YASMIN; ZURIANA SIREGAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Suwarno, Saidi AY, Yasmin Y, Siregar Z. 2025. Diversity and spatial distribution of dragonflies (Odonata) at Soraya Research Station, Leuser Ecosystem Area, Northern Sumatra, Indonesia. Biodiversitas 26: 681-689. Dragonflies (Odonata), a fascinating subject of study, are distributed from the tropics, subtropics to the temperate zones, and the type of habitat strongly influences their presence. This research, conducted from February to May 2021, holds substantial role as it aimed to investigate the dragonfly species in several habitats at the Soraya Research Station, Leuser Ecosystem Area, Northern Sumatra, Indonesia, and analyze their diversity index values. Samples were meticulously collected in the forest, scrub, and river habitats, which collected data from February to March between 9:00 am to 3:00 pm. Three different location points for each habitat were selected with five transect lines, each 200 m long and 5 m wide. The results showed that, dragonflies mostly distributed in the river, while the fewest species were found in the forest habitat. The total in all habitats, Libellulidae dominated both the number of species (39.6%; 19 species) and the number of individuals (30.4%; 129 individuals). In the Zygoptera suborder, the majority of species were from Chorocyphidae and Coenogridae, about 12.5%, meanwhile the number of individuals was in Calopterygidae (18.63%; 79 individuals). The species of dragonflies were found generally belonging to the category of least concern, but one of them is classified as an endangered species called Rhinocypha orea. The Shannon-Weiner diversity index (H') value of dragonflies in the three habitats was included in the moderate category, underscoring the importance of our findings.